Cu-catalyzed debrominative cyanation of gem-dibromoolefins: a facile access to alpha,beta-unsaturated nitriles - Ahuja, Brij Bhushan; Sudalai, Arumugam (Organic & Biomolecular Chemistry, 2015)
An efficient catalytic route for the synthesis of alpha,beta-unsaturated nitriles from easily accessible gem-dibromoolefins has been developed. The method utilized inexpensive reagents such as Cu2O as a catalyst, L-proline as a ligand and NaCN as a cyanide source to afford alpha,beta-unsaturated nitriles in high yields (62-86%). A deuterium exchange study has shown that one of the bromide atoms of gem-dibromoolefins exchanges with cyanide while the other with a deuterium atom.